2008
DOI: 10.1002/lsm.20623
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton excitation fluorescence microscopy of 5‐aminolevulinic acid induced fluorescence in experimental gliomas

Abstract: Multiphoton microscopy of 5-ALA induced PpIX fluorescence in brain tumor tissue conceptually provides a high resolution diagnostic tool, which in addition to structural information may also provide photochemical/functional information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…Yet the spectroscopy technique still needs to be validated in clinical routine. 6,10,23 Our data suggest a higher detection rate for tumor and infiltration zone in 5-ALA as opposed to iMRI. In Gd-DTPA-enhanced iMRI a high number of tumor-positive areas are missed.…”
Section: 29mentioning
confidence: 62%
“…Yet the spectroscopy technique still needs to be validated in clinical routine. 6,10,23 Our data suggest a higher detection rate for tumor and infiltration zone in 5-ALA as opposed to iMRI. In Gd-DTPA-enhanced iMRI a high number of tumor-positive areas are missed.…”
Section: 29mentioning
confidence: 62%
“…Cicchi et al [102] demonstrated enhanced tumor contrast and depth of imaging by using MAL-induced PpIX as the contrast agent, and two-photon excitation (TPE) in combination with FLIM as the imaging technique. A similar study by Kantelhardt et al [103] to identify gliomas achieved high contrast images of the glioma architecture that were easily discriminated from normal brain tissue, by detecting ALA-induced PpIX fluorescence with multiphoton microscopy. A few other studies report the use of multiphoton excitation for PpIX detection [104], but offer no detailed spectral information.…”
Section: Approaches For Measuring Ppix Beneath the Surface Of The Skinmentioning
confidence: 94%
“…This suggests that the photochemical analysis may offer means for specific detection of residual tumour in biopsy specimens, which may increase the diagnostic value of this technique. We have further demonstrated that the specificity of tumour cell detection by multi-photon microscopy may be significantly increased by detection of 5-ALA induced PpIX fluorescence in experimental gliomas [7]. The fluorescence lifetime analysis of induced PpIX fluorescence by multi-photon microscopy demonstrated that PpIX fluorescence was significantly prolonged compared to fluorescence of endogenous fluorophores.…”
Section: Discussionmentioning
confidence: 74%